Proposed Integrated Marketing Communication Strategy to Promote Brand Awareness of Online Learning Portals: Study of MOJADIAPP.COM - Mietra, Andhika Bayu; Wibowo, Satya Aditya (AIBPM Publisher, 2022)
Indonesia as one of the largest countries in the world, with a projected population of 274 million people in 2020, will enjoy a demographic dividend in 2030-2040. Amidst the Covid-19 Pandemic, this opens new opportunities for those in the education sector to develop a feasible business in online learning. New players in the online learning industry face tough competition with over 200 existing local brands in the country. Strong brand awareness is needed to be recognized and thus compete in the existing competition. This paper aims to find an appropriate marketing strategy to improve brand awareness. For analysis, the researchers use a market survey to understand the preferred marketing strategy from a customer’s point of view, and interviews with the founders of Mojadiapp.com, a newly developed online learning portal based in Indonesia, understand the internal and external condition of the company. The study shows that Integrated Marketing Communication could help improve brand awareness for these new players.